Regressão auditiva: o impedimento da música como conhecimento em Th. Adorno - Felicio Ramalho Ribeiro (2009)
The aim of our study was to understand how the regression of listening, thought by Adorno, prevents the assimilation by the individual of a knowledge regarding reality from music. We start by investigating the psychoanalytic origin of the concept of regression and the establishment of similarities and distinctions between this concept and its philosophical correlate, initially prepared by Adorno in the On the fetish character in music and the regression of listening. In the section forward, we analyze the extremely regressive potential of the Stravinsky´s aesthetic proposal from the notes of the philosopher in the Philosophy of new music. The final chapter seeks to highlight how the music of Schönberg is built itself as a distinct vehicle of knowledge and how its reception is blocked before the degenerative trend stimulated by Stravinsky.